Participatory Governance in the EU Enhancing or Endangering Democracy and Efficiency? - Lindgren, K. (Palgrave Studies in European Union Politics,, 2011)
An empirical assessment of whether participatory governance reforms within the EU enhance or endanger democracy. Many consider allowing civil society to take an active role in EU policy-making to offer the most effective means of enhancing democracy in the EU, whereas others argue that such attempts deepen the EU's democratic deficit.